(untitled) (Vietnam Journal of Community Medicine, 2025)
Purpose: To evaluate the users’ feelings after two months of using Magnesium alkaline ionized water. Methods: cross-sectional descriptive study, using questionnaires on 134 people in Cam Thanh commune, Cam Lo district, Quang Tri province after two months of using Magnesium alkaline ionized water. Results: 90.3% did not notice any unusual smell when drinking; 51.5% did not notice any difference between alkaline ionized water and regular filtered water, 21.1% found it sweeter, 15.7% found it cooler and 9.7% found it more fishy than regular water. 93.3% found the water clear and colorless. 52.2% of the study subjects had positive feelings, including: 22.4% found it easier to digest, 17.9% found it effective for weight loss, 11.9% found their skin more beautiful. Some signs of risk of digestive, cardiovascular and neurological diseases were reduced Some common health complaints related to the digestive, cardiovascular, and nervous systems were relieved. Conclusions: The majority of research subjects after two months of initial use of alkaline magnesium ionized water had generally positive feelings.